Employee empowerment, organizational commitment and innovative behaviour as contemporary management practices in reshaping human capital - Sudha, S. (University of Jaffna, 2019)
In the contemporary business environment, human resource (HR) is an indispensable input for organizational effectiveness. Hence, an effective management of human resources has an important role to play in the performance and success of organizations and they play a vital role in shaping and reshaping the human capital too. It is important that business organizations need to empower employees which develops commitment towards the organization. Committed employees work hard for attaining the goals of the organization and also lead the organization to innovation. Most of the organizations follow employee empowerment, organizational commitment and innovative behaviour as the best practices in their organizations. In this paper the author tries to explore the relationship among employee empowerment, organizational commitment and innovative behaviour. The study was carried out in 3 Information technology organizations in Chennai. 159 respondents participated in the study.The collected data was captured in SPSS 16 and AMOS for CFA. Correlation analysis proves correlations among the variables are significant. Regression analysis provides model identified but statistical points proved to be weak on the variables taken for the study.The study identified that employee empowerment and organizational commitment have been practiced as contemporary human resource practices leads to employee innovative behaviour.
Keywords: Contemporary business; Employee empowerment; Organizational commitment; Innovative behaviour